2013
DOI: 10.1002/cbic.201300175
|View full text |Cite
|
Sign up to set email alerts
|

Structures of KOD and 9°N DNA Polymerases Complexed with Primer Template Duplex

Abstract: Replicate it: Structures of KOD and 9°N DNA polymerases, two enzymes that are widely used to replicate DNA with highly modified nucleotides, were solved at high resolution in complex with primer/template duplex. The data elucidate substrate interaction of the two enzymes and pave the way for further optimisation of the enzymes and substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 65 publications
5
76
0
2
Order By: Relevance
“…The family-B DNA polymerases from the Thermococcales order of the archaea are especially favored for PCR, due to their extreme stability at elevated temperatures and the presence of fidelity-conferring 3′-5′ exonuclease activity (Lundberg et al, 1991; Cline et al, 1996; Takagi et al, 1997; Nishioka et al, 2001). Both the amino acid sequences and X-ray structures of these polymerases demonstrate a high degree of similarity, with structures available for the enzymes isolated from Thermococcus gorgonarius (Tgo-Pol) (Hopfner et al, 1999; Firbank et al, 2008; Killelea et al, 2010), Thermococcus kodakarensis (Tkod-Pol) (Hashimoto et al, 2001; Kuroita et al, 2005; Bergen et al, 2013), Thermococcus species 9°N-7 (9°N-Pol) (Chapin-Rodriguez et al, 2000), Pyrococcus furiosus (Pfu-Pol) (Kim et al, 2008) and Pyrococcus abysii (Pab-Pol) (Gougel et al, 2012). Despite similarities of amino acid sequence and structure, these polymerases have diverse kinetic properties; a strong influence on PCR performance.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The family-B DNA polymerases from the Thermococcales order of the archaea are especially favored for PCR, due to their extreme stability at elevated temperatures and the presence of fidelity-conferring 3′-5′ exonuclease activity (Lundberg et al, 1991; Cline et al, 1996; Takagi et al, 1997; Nishioka et al, 2001). Both the amino acid sequences and X-ray structures of these polymerases demonstrate a high degree of similarity, with structures available for the enzymes isolated from Thermococcus gorgonarius (Tgo-Pol) (Hopfner et al, 1999; Firbank et al, 2008; Killelea et al, 2010), Thermococcus kodakarensis (Tkod-Pol) (Hashimoto et al, 2001; Kuroita et al, 2005; Bergen et al, 2013), Thermococcus species 9°N-7 (9°N-Pol) (Chapin-Rodriguez et al, 2000), Pyrococcus furiosus (Pfu-Pol) (Kim et al, 2008) and Pyrococcus abysii (Pab-Pol) (Gougel et al, 2012). Despite similarities of amino acid sequence and structure, these polymerases have diverse kinetic properties; a strong influence on PCR performance.…”
Section: Introductionmentioning
confidence: 75%
“…However, superimposition of the structures of the two polymerases (Figure 1C) shows that R381 in Tkod-Pol and L381 in Pfu-Pol are spatially equivalent, suggesting the alternative alignment shown in Figure 1B (Hashimoto et al, 2001). Another region that may contribute to processivity is the thumb domain, responsible for binding double-stranded DNA (Firbank et al, 2008; Killelea et al, 2010; Gougel et al, 2012; Bergen et al, 2013). This domain grips DNA tightly and interacts with newly synthesized double-strands, implying an important role in DNA translocation.…”
Section: Introductionmentioning
confidence: 99%
“…The structural coordinates for KOD DNA polymerase complexed with duplex DNA were obtained from the crystal structure PDB ID: 4K8Z [36] (with resolution of 2.29 Å). KOD-dTTP model was built based on the 1IG9 coordinates using Prime module (a homology modelling tool) of Schrödinger suite, as there was no structure available with the incoming triphosphates for KOD DNA polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…Both Euryarchaeota and Crenarchaeota encode family B DNA pols. Family B DNA pols share similar structures to the phage RB69 DNA pol (Wang et al 1997) as demonstrated for the structures of the family B archaeal DNA pols from Thermococcus gorganarius (Tgo) (Firbank et al 2008;Hopfner et al 1999;Killelea et al 2010), Thermococcus kodakarensis (KOD1) (Bergen et al 2013;Hashimoto et al 2001;Kuroita et al 2005), Thermococcus species 9°N-7 (9°N-7) (Rodriguez et al 2000), Pyrococcus furiosus (Pfu) (Kim et al 2008), and Pyrococcus abysii (Pab) (Gouge et al 2012), there are five protein domains. The structure for the Tgo DNA pol, which was the first solved structure for an archaeal DNA pol, is shown in Fig.…”
Section: Introductionmentioning
confidence: 96%